2020
DOI: 10.22441/sinergi.2020.3.001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cutting Speed in the Turning Process of Aisi 1045 Steel on Cutting Force and Built-Up Edge (Bue) Characteristics of Carbide Cutting Tool

Abstract: In the machining of metal cutting, cutting tools are the main things that must be considered. Using improper cutting parameters can cause damage to the cutting tool. The damage is Built-Up Edge (BUE). The situation is undesirable in the metal cutting process because it can interfere with machining, and the surface roughness value of the workpiece becomes higher. This study aimed to determine the effect of cutting speed on BUE that occurred and the cutting strength caused. Five cutting speed variants are used. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Applying cutting insert grade UTi20T under MQL conditions enhances efficiency, tool life, and cutting results for several reasons. However, research [24] focuses on cutting speed in the cutting process by increasing the cutting parameters to determine the level of roughness of the surface of the object to be cut by paying attention to the occurrence of built-up edge (BUE) in MQL conditions, so the cutting process must be stopped. This still requires some important information in the form of parameters such as cutting force, power consumed, tool wear development, and others.…”
Section: Introductionmentioning
confidence: 99%
“…Applying cutting insert grade UTi20T under MQL conditions enhances efficiency, tool life, and cutting results for several reasons. However, research [24] focuses on cutting speed in the cutting process by increasing the cutting parameters to determine the level of roughness of the surface of the object to be cut by paying attention to the occurrence of built-up edge (BUE) in MQL conditions, so the cutting process must be stopped. This still requires some important information in the form of parameters such as cutting force, power consumed, tool wear development, and others.…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, this study shows cutting fluids impact was least insignificant among all the parameters whose probability value was 0.2780. Sobron et al [26] focused on built up edge formation on cutting tool with respect to cutting speed variation during turning of AISI 1045 steel. They observed that BUE formation was not directly persuade by cutting speed.…”
Section: Introductionmentioning
confidence: 99%